2010
DOI: 10.1177/0017896910373170
|View full text |Cite
|
Sign up to set email alerts
|

What factors are important in smoking cessation amongst deprived communities?

Abstract: Objective: There is limited evidence regarding effective smoking cessation interventions in deprived communities. This study explored what factors are considered most important in smoking cessation, from the perspective of a group of NHS Stop Smoking Service users from a deprived community. Design: A qualitative study. Setting: A deprived community in Brighton and Hove City, Southeast England. Methods: Fifteen adults who had used the local NHS Stop Smoking Service were recruited to the focus groups. Thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…This is consistent with previous research which has shown that fear of health professional judgement can act as a barrier for disadvantaged smokers to access smoking cessation services [22,23]. Several women felt that group sessions were highly valuable, notably in the support, advice and shared experiences provided from attending the groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous research which has shown that fear of health professional judgement can act as a barrier for disadvantaged smokers to access smoking cessation services [22,23]. Several women felt that group sessions were highly valuable, notably in the support, advice and shared experiences provided from attending the groups.…”
Section: Discussionsupporting
confidence: 89%
“…Meta-analysis of randomised control trials shows quit attempts are more successful when a smoking cessation facilitator is combined with nicotine replacement therapy (NRT) or other cessation therapies [30]. The cost of smoking cessation aids has also been shown to be a deterrent for people from deprived communities [23]. Evidence suggests that utility of NRTs is particularly important for women.…”
Section: Discussionmentioning
confidence: 99%
“…Overall (see Figure 1), our literature search revealed that lower SES smokers find it more difficult to quit because of severe nicotine addiction [9,10], strong smoking habits, and the absence of alternative behaviors that can replace smoking [9,38,39]. Also, they experience low self-efficacy and coping skills [10,40], low social support for quit attempts [10,29,39,41], and a strong prosmoking social norm [38,42]. In addition, lower SES smokers are often unfamiliar with the services available [43,44] and tend to have negative attitudes towards smoking cessation support (e.g., perceiving support as ineffective and expensive) [9,43,45].…”
Section: Exploration Phasementioning
confidence: 99%
“…Important reasons to smoke include coping with povertyrelated stress [10,38], loneliness and boredom [9,42], and weight-gain prevention [39]. Additional needs indicated by lower SES smokers included peer support [10,29,41] and support regarding material and social circumstances [42,[46][47][48].…”
Section: Exploration Phasementioning
confidence: 99%
See 1 more Smart Citation